2014
DOI: 10.1001/jama.2014.3314
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors vs Conventional Chemotherapy in Non–Small Cell Lung Cancer Harboring Wild-Type Epidermal Growth Factor Receptor

Abstract: Among patients with advanced NSCLC harboring WT EGFR, conventional chemotherapy, compared with first-generation EGFR TKI, was associated with improvement in PFS but not overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 44 publications
1
81
1
3
Order By: Relevance
“…A recent study examined 23 randomized trials of EGFR tyrosine kinase inhibitors in non-small cell lung cancer. 8 This meta-analysis of 14 570 patients found EGFR mutations sensitive to tyrosine kinase inhibitor therapy in 31% of patients (n ¼ 4473). The EGFR mutation status was predictive of progression-free survival, but the tyrosine kinase inhibitor treatment had no impact on overall survival for patients despite their EGFR mutation status.…”
Section: Lessons From Early Targeted Therapiesmentioning
confidence: 97%
“…A recent study examined 23 randomized trials of EGFR tyrosine kinase inhibitors in non-small cell lung cancer. 8 This meta-analysis of 14 570 patients found EGFR mutations sensitive to tyrosine kinase inhibitor therapy in 31% of patients (n ¼ 4473). The EGFR mutation status was predictive of progression-free survival, but the tyrosine kinase inhibitor treatment had no impact on overall survival for patients despite their EGFR mutation status.…”
Section: Lessons From Early Targeted Therapiesmentioning
confidence: 97%
“…Patients with squamous cell carcinoma or NSCLC who do not harbor an EGFR mutation revealed a benefit from TKI compared with the best supportive care as second-line treatment (25)(26)(27)(28). However, previous meta-analyses reported that cytotoxic chemotherapy is better compared with TKI for patients without EGFR mutations (29)(30)(31).…”
Section: All Patients -----------------------------------------------mentioning
confidence: 99%
“…For patients with advanced NSCLC that exhibit a negative or unknown EGFR mutational status or ALK rearrangements, platinum-based double chemotherapy is the typical first-line therapy (3,4). In the treatment of non-squamous cell carcinoma, pemetrexed combined with platinum demonstrates a significantly improved toxicity profile and OS, compared with taxane-or gemcitabine-based regimes (3,5,6).…”
Section: Introductionmentioning
confidence: 99%